Stability of Mammalian Erythrocytes Under Varying Osmotic Conditions of the Medium - Chabanenko, Olena; Yershova, Natalia; Yershov, Serhii; Shpakova, Nataliia (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):291